Biomarkers in toxicology - Gupta, Ramesh C. (Ramesh Chandra), 1949- (Academic Press, 2019)
Biomarkers in Toxicology, Second Edition, is a timely and comprehensive reference dedicated to all aspects of biomarkers that relate to chemical exposure and their effects on biological systems. This revised and completely updated edition includes both vertebrate and non-vertebrate species models for toxicological testing and the development of biomarkers. Divided into several key sections, this reference volume contains new chapters devoted to topics in microplastics, neuroimmunotoxicity and nutraceuticals, along with a look at the latest cutting-edge technologies used to detect biomarkers. Each chapter contains several references to current literature and important resources for further reading. Given this comprehensive treatment, this book is an essential reference for anyone interested in biomarkers across the scientific and biomedical fields.